2012
DOI: 10.1111/j.1744-7348.2012.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant responses to water deficit by drought‐tolerant and ‐sensitive sugarcane varieties

Abstract: Water deficit is the major yield‐limiting factor of crop plants. The exposure of plants to this abiotic stress can result in oxidative damage due to the overproduction of reactive oxygen species. The aim of this work was to study the antioxidant‐stress response of drought‐tolerant (SP83‐2847 and SP83‐5073) and drought‐sensitive (SP90‐3414 and SP90‐1638) sugarcane varieties to water‐deficit stress, which was imposed by withholding irrigation for 3, 10 and 20 days. The drought‐sensitive varieties exhibited the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
2
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 103 publications
9
107
2
5
Order By: Relevance
“…Similar results have been associated with tolerance to water deficiency in wheat (SAIRAM et al, 1998) and to salinity in sugarcane (WILLADINO et al, 2011). Increase or maintenance of APX and CAT activities indicates the importance of these enzymes in H 2 O 2 detoxification and protection against oxidative damage (CIA et al, 2012).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Similar results have been associated with tolerance to water deficiency in wheat (SAIRAM et al, 1998) and to salinity in sugarcane (WILLADINO et al, 2011). Increase or maintenance of APX and CAT activities indicates the importance of these enzymes in H 2 O 2 detoxification and protection against oxidative damage (CIA et al, 2012).…”
Section: Resultssupporting
confidence: 72%
“…In the triple stress combination, an increase in MDA content was observed in RB98710. Low MDA levels are representative of tolerance in sugarcane genotypes exposed to water deficiency (CIA et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Relative water content (RWC) was analyzed on the 31 st DAT at 12h00, following the methodology of Cia et al (2012). One foliar segment (2 cm length × 2 cm width) was collected from the middle portion of young fully expanded leaves from each plot, properly stored in plastic bags and cooled to avoid tissue dehydration until analysis in the laboratory.…”
Section: Evaluated Traitsmentioning
confidence: 99%
“…The economy in water and nutrients for plant cultivation will depend on the efficiency of the sensorbased controllers for irrigation to avoid either drainage or drought, which causes waste of water or growth limitation, respectively (Cia et al, 2012;Boaretto et al, 2014;Medici et al, 2014). The lack of such controllers at a low cost and ready to be used in commercial conditions may explain why precise irrigation is rarely used for growing plants in pots, as most use timers or manual control (Montesano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These data corroborate those observed by Willadino et al (2011), who evaluated the salt stress on the variety RB861515 and observed a more efficient mechanism in the protection of the plant against the action of reactive oxygen species, particularly H 2 O 2 , due to the increase in the activities of the enzymes CAT and APX. The increase in APX and CAT activity indicates the importance of these enzymes in the detoxification of H 2 O 2 and protection against oxidative damages (Cia et al, 2012). Morais (2013), studying the combined action of abiotic stress factors, reported that the enzymatic behavior of the variety RB867515 was efficient in the regulation and detoxification of the ROS produced in the plant cell, indicating a greater tolerance of this variety to the different types of stress.…”
Section: Bmentioning
confidence: 99%